Implikasi Model Pembelajaran Untuk Melatih Keterampilan Sosial Emosional Anak Usia Dini di TK YAPIS - Ferry Irawan; Dharma Gyta Sari Harahap; Muh. Rafi'y; Cristiana Normalita de Lima (Yayasan Perguruan Kampus, 2024)
The community service aims to provide direct implications in the world of education. The community service is carried out through a direct learning process at school so that the implications can directly train children's social-emotional skills continuously. Each learning activity is adjusted to the derivation of each indicator of social emotional skills as an interconnected part. The results of the community service explain that innovative learning models can train children's social emotional skills holistically, and directly train 21st century skills.